DRUG UTILIZATION AND DRUG INTERACTIONS IN PATIENTS WITH CHRONIC HEART FAILURE HOSPITALIZED AT VINH CHAU TOWN MEDICAL CENTER IN 2023 (Vietnam Journal of Community Medicine, 2026)
Background:Chronic heart failure is a common cardiovascular disease that requires long-term treatment with multiple drug combinations. The use of polypharmacy increases the risk of drug–drug interactions, which may affect treatment effectiveness and patient safety. Therefore, assessing patterns of drug use and drug–drug interactions in the management of chronic heart failure is necessary.Objectives: To investigate drug utilization patterns and analyze drug–drug interactions among hospitalized patients with chronic heart failure at Vinh Chau Town Medical Center, Soc Trang Province, in 2023.Materials and Methods: A retrospective cross-sectional descriptive study was conducted on 356 medical records of patients diagnosed with chronic heart failure and treated as inpatients from January 1, 2023 to December 31, 2023. Drug–drug interactions were evaluated using Micromedex and Drug Interaction Facts databases.Results: Angiotensin-converting enzyme inhibitors (ACEIs) were the most frequently used drug group (33.71%). Regimens combining two drug classes accounted for the highest proportion (32.30%). Clinically significant drug–drug interactions accounted for 32.44%, predominantly classified as severe interactions (67.67%) and mainly related to pharmacodynamic mechanisms (64.82%). The most common interacting drug pairs involved spironolactone, digoxin, furosemide, and captopril, with the spironolactone–digoxin combination being the most frequent (4.48%).Conclusion: ACE inhibitors were commonly prescribed, and two-drug combination regimens predominated in the treatment of chronic heart failure. Drug–drug interactions were mainly pharmacodynamic in nature, with a considerable proportion classified as severe, particularly involving spironolactone, digoxin, furosemide, and captopril.
Keywords: Polypharmacy, chronic heart failure, drug interactions.